2020
DOI: 10.1002/path.5402
|View full text |Cite
|
Sign up to set email alerts
|

Recent advances in the biology of tumour hypoxia with relevance to diagnostic practice and tissue‐based research

Abstract: In this review article, we examine the importance of low levels of oxygen (hypoxia) in cancer biology. We provide a brief description of how mammalian cells sense oxygen. The hypoxia-inducible factor (HIF) pathway is currently the best characterised oxygen-sensing system, but recent work has revealed that mammals also use an oxygen-sensing system found in plants to regulate the abundance of some proteins and peptides with an amino-terminal cysteine residue. We discuss how the HIF pathway is affected during the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
20
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(20 citation statements)
references
References 204 publications
(230 reference statements)
0
20
0
Order By: Relevance
“…In addition hypoxia has a wellestablished role as a microenvironmental factor promoting metastasis 19 . Of separate note, ccRCC is additionally uniquely characterised by oxygen-independent so called "pseudohypoxia" as a universal feature of the disease due to VHL inactivation 20 . Clinically, necrosis is associated with ischemia, either as a chronic process resulting in gradual tissue damage, or as an acute event such as infarction related to arterial or venous thrombosis.…”
Section: Discussionmentioning
confidence: 99%
“…In addition hypoxia has a wellestablished role as a microenvironmental factor promoting metastasis 19 . Of separate note, ccRCC is additionally uniquely characterised by oxygen-independent so called "pseudohypoxia" as a universal feature of the disease due to VHL inactivation 20 . Clinically, necrosis is associated with ischemia, either as a chronic process resulting in gradual tissue damage, or as an acute event such as infarction related to arterial or venous thrombosis.…”
Section: Discussionmentioning
confidence: 99%
“…How do we accurately measure hypoxia? The interested reader is referred to the excellent review by Macklin et al (60).…”
Section: Discussionmentioning
confidence: 99%
“…HIF1 is overexpressed in a variety of solid tumors [ 13 ]. Moreover, our previous study indicated that HIF1 was overexpressed and possibly mediated hypoxia-induced autophagic activation in human OS tissues [ 14 ].…”
Section: Discussionmentioning
confidence: 99%